Monitoring Expression of Cytochrome P450 Genes During Postischemic Rat Liver Reperfusion Using DNA Microarrays - Yasuo Takahashi; Yayoi Nishida; Yukimoto Ishii; Koichi Ishikawa; Satoshi Asai (Elsevier, 2005)
We investigated the expression of 50 cytochrome P450 (CYP) genes in the post-ischemic reperfused rat liver using a DNA microarray. Thirteen CYPs showed absent expression in all experiments and 2 CYPs were induced by pentobarbital, which was used as an anesthetic. Eight of the remaining 35 CYPs showed significantly decreased expression following ischemia-reperfusion. Monitoring CYP expression may be a powerful approach for elucidation of pathways regulating drug metabolism that may be involved in postischemic reperfusion liver injury. Keywords:: cytochrome P450, postischemic liver reperfusion, gene expression